Чернігівський губернський архітектор Михайло Степанович Щитинський - Тригуб, О. (Сiверянський лiтопис, 2015)
Висвітлюється життєвий шлях та діяльність на посаді чернігівського губернського архітектора статського радника М. С. Щитинського (1816 – ?). На основі архівних джерел, які вперше запроваджуються у науковий обіг, з’ясовані невідомі
факти його походження та біографії. В статье освещен жизненный путь и деятельность на должности черниговского
губернского архитектора статского советника М. С. Щитинского (1816 – ?). На
основе архивных источников, которые впервые вводятся в научный оборот, выяснены
неизвестные факты его происхождения и биографии. The article highlights the life and activities of M. S. Shchytynsky (1816–?), who
occupied the position of Chernigov Provincial Architect for 15 years, and took an active
part in the construction of Chernigov and other settlements of the province. It was found
that his ancestors came from the Polish nobility and moved to the Left Bank Ukraine at the
turn of 17th–18th centuries. M. S. Shchytynsky received a good education at the School of
Civil Engineers, after which he served at the Chernigov Provincial Construction and Road
Commission. Moving up the career ladder, M.S. Shchytynsky was appointed Chernigov
Provincial Architect on 20 June 1850. An analysis of archival sources allowed the author
to conclude that M. S. Shchytynsky fulfilled his tasks with deep and professional approach.